PENGARUH KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR DI UPPD BANJARMASIN 1 - Rakhmi Ridhawati; Dewi Lesmanawati; Annisa Pratiwi Lufty (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2022)
This study aims to empirically proved the effect of service quality on taxpayer compliance in paying motor vehicle taxes at UPPD Banjarmasin 1. The population used in this study was motorized vehicle taxpayers at UPPD Banjarmasin 1 and is classified as an effective taxpayer in 2019. The population in this study were 154,626 taxpayers in UPPD Banjarmasin 1. By using the Slovin formula, the selected sample is 400 respondents. The research method used a quantitative method, with the results of the study showing that the Quality of Tax Services has an effect on Taxpayer Compliance in Paying Motor Vehicle Taxes at UPPD Banjarmasin1.